(untitled) (Global Journals of Research in Engineering, 2023)
Atmospheric tank projects cover a wide range of technical characteristics ranging from their purpose according to the regulatory framework the type of product stored the technical characteristics of the tank to serve this storage with structural safety and finally the devices and technical resources to make the equipment financially and economically viable and sustainable As a basis for criteria for this assessment the correct regulatory framework for each type of tank based on its application as well as the correct selection of material for its performance and life expectancy were addressed Performance improvement criteria were also evaluated such as the correct sizing of the tank inlet outlet and vent nozzles the use of sensors and devices and equipment to avoid overpressure or vacuum and the use of internal floating roofs In addition environmental criteria were also presented such as the correct selection of tank colors and the assessment of their area of incidence of solar radiation The list of criteria and technical performance and environmental details can be further complemented and developed with other characteristics of the tanks and the objective of this article was to evaluate the main parameters of analysis to guide the developer of the tank project to execute it seeking to optimize technical data with immediate execution and operating costs and the environmental impact of project decisions for welded vertical cylindrical atmospheric storage tanks